2018
DOI: 10.1080/14756366.2017.1419219
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of novel oridonin analogues as potent anticancer agents

Abstract: To identify anticancer agents with higher potency and lower toxicity, a series of oridonin derivatives with substituted benzene moieties at the C17 position were designed, synthesised, and evaluated for their antiproliferative properties. Most of the derivatives exhibited antiproliferative effects against AGS, MGC803, Bel7402, HCT116, A549, and HeLa cells. Compound 2p (IC50 = 1.05 µM) exhibited the most potent antiproliferative activity against HCT116 cells; it was more potent than oridonin (IC50 = 6.84 µM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…An ent-kaurane diterpenoid isolated from Isodon rubescens, Oridonin (Ori) and its analogs exert anti-tumor potential in cancer cells (2325). Besides, the mechanisms involved are mainly concentrated on autophagy and apoptosis (26, 27).…”
Section: Introductionmentioning
confidence: 99%
“…An ent-kaurane diterpenoid isolated from Isodon rubescens, Oridonin (Ori) and its analogs exert anti-tumor potential in cancer cells (2325). Besides, the mechanisms involved are mainly concentrated on autophagy and apoptosis (26, 27).…”
Section: Introductionmentioning
confidence: 99%
“…The cytotoxicity of EL, MEL and compounds 1–6 on two cancer cell lines was determined by MTT assay. 22 The cells were seeded in five-well plates (1 × 10 4 cells per well) and incubated at 37 °C for 24 h. The cells were then treated with EL, MEL, cisplatin and compounds 1–6 at different concentrations (0.1–100 μmol L −1 ). Cisplatin was used as the positive control.…”
Section: Methodsmentioning
confidence: 99%
“…9B). The structure-activity results revealed that the hydroxy-substituted compounds at C-20 (20 (S/R)-Rg 3 ) had the hemostatic activities, while Rk 1 , SFt 3 and Rg 5 with double bond at D20 (21) or D20 (22) played the anticoagulant activities. The anticoagulant activity of the MEL increased due to increases in the concentrations of Rk 1 , Rg 5 , and SFt 3 .…”
Section: The Anticoagulant Effect Of the Transformation Products In Vmentioning
confidence: 99%
“…Nonetheless, Shen et al (2018) demonstrated that α, β-unsaturated ketones can be targets for structural modifications to achieve promising derivatives. Shen’s group synthesized oridonin derivatives with substituted benzene moieties at the C17 position, and compound 16 (listed in Table 3 ) proved to be the most potent with an IC 50 value of 1.05 μM against the HCT-116 cell line.…”
Section: Oridonin Derivatives: Potential Agents In Anticancer Therapymentioning
confidence: 99%